Clinical characteristics of familial hypocalciuric hypercalcaemia type 1: A multicentre study of 77 adult patients. (14th May 2020) - Mouly, Céline; Vargas‐Poussou, Rosa; Lienhardt, Anne; Silve, Caroline; Hureaux, Marguerite; Magdelaine, Corinne; Buffet, Alexandre; Grunenwald, Solange; Kuhn, Jean-Marc; Brue, Thierry; Reznik, Yves; Tabarin, Antoine; et al.
Abstract: Objective: Familial hypocalciuric hypercalcaemia type 1 (FHH1), related to heterozygous loss‐of‐function mutations of the calcium‐sensing receptor gene, is the main differential diagnosis for primary hyperparathyroidism. The aim of our study was to describe clinical characteristics of adult patients living in France with a genetically confirmed FHH1. Design and patients: This observational, retrospective, multicentre study included 77 adults, followed up in 32 clinical departments in France, with a genetic FHH1 diagnosis between 2001 and 2012. Results: Hypercalcaemia was diagnosed at a median age of 53 years [IQR: 38‐61]. The diagnosis was made after clinical manifestations, routine analysis or familial screening in 56, 34 and 10% of cases, respectively, (n = 58; data not available for 19 patients). Chondrocalcinosis was present in 11/51 patients (22%), bone fractures in 8/56 (14%) and renal colic in 6/55 (11%). The median serum calcium was 2.74 mmol/L [IQR: 2.63‐2.86 mmol/L], the median plasma parathyroid hormone level was 4.9 pmol/L [3.1‐7.1], and the median 24‐hour urinary calcium excretion was 2.8 mmol/24 hours [IQR: 1.9‐4.0]. Osteoporosis (dual X‐ray absorptiometry) or kidney stones (renal ultrasonography) were found in 6/38 patients (16%) and 9/32 patients (28%), respectively. Fourteen patients (18%) underwent parathyroid surgery; parathyroid adenoma was found in three patients (21%) and parathyroid hyperplasia in nine patients (64%). No correlation between genotype and phenotype was established. Conclusion: This large cohort study demonstrates that FHH1 clinical characteristics can be atypical in 33 patients (43%). Clinicians should be aware of this rare differential diagnosis in order to adopt an appropriate treatment strategy.